Directional Charge-Carrier Transport in Oriented Benzodithiophene Covalent Organic Framework Thin Films - Medina, Dana D; Petrus, Michiel L; Jumabekov, Askhat N; Margraf, Johannes T; Weinberger, Simon; Rotter, Julian M; Clark, Timothy; Bein, Thomas (ACS nano, 2017)
Charge-carrier transport in oriented COF thin films is an important factor for realizing COF-based optoelectronic devices. We describe how highly oriented electron-donating benzodithiophene BDT-COF thin films serve as a model system for a directed charge-transport study. Oriented BDT-COF films were deposited on different electrodes with excellent control over film roughness and topology, allowing for high-quality electrode–COF interfaces suitable for device fabrication. Hole-only devices were constructed to study the columnar hole mobility of the BDT-COF films. The transport measurements reveal a clear dependency of the measured hole mobilities on the BDT-COF film thickness, where thinner films showed about two orders of magnitude higher mobilities than thicker ones. Transport measurements under illumination yielded an order of magnitude higher mobility than in the dark. In-plane electrical conductivity values of up to 5 × 10–7 S cm–1 were obtained for the oriented films. Impedance measurements of the hole-only devices provided further electrical description of the oriented BDT-COF films in terms of capacitance, recombination resistance, and dielectric constant. An exceptionally low dielectric constant value of approximately 1.7 was estimated for the BDT-COF films, a further indication of their highly porous nature. DFT and molecular-dynamics simulations were carried out to gain further insights into the relationships between the COF layer interactions, electronic structure, and the potential device performance.